The Great Recession and the Health of Young Children: A Fixed-Effects Analysis in Ireland. Issue 7 (12th January 2018) - Reinhard, Erica; Layte, Richard; McCrory, Cathal; Panico, Lidia; Avendano, Mauricio
Abstract: Economic recessions have been linked to adult health, but few studies have examined how recessions influence the health of young children. This study examined the impact of life transitions linked to the recent financial crisis on the health of young children in Ireland. Data came from the Growing Up in Ireland Infant Cohort Study ( n = 11, 134), which assessed children before (2008), during (2011), and after (2013) the Great Recession that followed the financial crisis of 2008 and incorporated questions on the impacts of the financial crisis on families. Using fixed-effects models to control for confounding, we found that a reduction in welfare benefits during the recession was associated with a significant increase in the risks of asthma (β = 0.014, 95% confidence interval (95% CI): 0.004, 0.023) and atopy (β = 0.014, 95% CI: 0.001, 0.027). While parental job loss was not associated with child health, a reduction in working hours was associated with increased reports of child health problems (β = 0.024, 95% CI: 0.004, 0.043), as were difficulties affording basic necessities (β = 0.019, 95% CI: 0.001, 0.038). Results suggest that failing to protect vulnerable families and children during economic recessions may have long-lasting implications for child health.